The Impact of High School Teacher Behaviors on Student Aggression - Angela Spaulding (Arizona State University, 2015)
Aggressive student behaviors are of concern to every school in the nation. Discovering ways to help teachers prevent and/or respond to such student behavior is of great importance. This reported research sought to discover if and how teacher behaviors impact student aggression in the classroom. In doing so, the researcher did not set out to blame teachers for student aggression; the goal was to discover how teachers might modify behavior and react in ways that will help create positive and peaceful classroom environments and prevent student aggressive behaviors that can result in violence.